2013
DOI: 10.1016/j.bbi.2012.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity increases vulnerability for behavioral symptoms and immune dysregulation in women with breast cancer

Abstract: Women respond differentially to the stress-associated with breast cancer diagnosis and treatment, with some women experiencing more intense and/or sustained behavioral symptoms and immune dysregulation than others. Childhood adversity has been identified to produce long-term dysregulation of stress response systems, increasing reactivity to stressors encountered during adulthood. This study determined whether childhood adversity increased vulnerability for more intense and sustained behavioral symptoms (fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 109 publications
1
67
0
Order By: Relevance
“…As examples, an unremitting an chronic course is associated with cortisol differences (96), poor sleep (97), avoidant coping style (98), socioeconomic position (99), and childhood abuse and neglect (100). For example, childhood physical neglect predicted chronic courses of depression (101) after depression had developed in those with a breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…As examples, an unremitting an chronic course is associated with cortisol differences (96), poor sleep (97), avoidant coping style (98), socioeconomic position (99), and childhood abuse and neglect (100). For example, childhood physical neglect predicted chronic courses of depression (101) after depression had developed in those with a breast cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…These findings contradict extensive animal and human literature suggesting a powerfully detrimental effect of maternal separation on biological profiles (e.g., Refs. (60,61)) and preliminary evidence that physical neglect is associated with elevated IL-6 in breast cancer survivors (25). This may be because the Risky Families questionnaire assesses a lack of affection, rather than physical neglect or separation from a parent.…”
Section: Discussionmentioning
confidence: 99%
“…The Risky Families questionnaire was based on questions from a foundational study that demonstrated a dose-response relationship between early adverse experiences and disease incidence in a sample of 10,000 adults (14), and bolstered with questions developed through qualitative interviews (42). Previous work has shown associations between the Risky Families scale and biological outcomes (42,64–66); however, it does not assess all forms of childhood adversity including sexual abuse, physical neglect, and low socioeconomic status, which have been linked to increased adulthood inflammation (19,25,37,51). Chronicity and timing of adverse experiences also likely influence their impact, although these dimensions are not captured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated women with early stage breast cancer to report high levels of fatigue after surgery and during cancer treatment (14). Such fatigue may be attributed to sleep disturbance, which is more prevalent and intense prior to treatment onset and during the early weeks of treatment (15).…”
Section: Introductionmentioning
confidence: 99%